Localizing Islamic Law: Marriage Practices and the Pak Ponjen Tradition in Kudus - Ngazizah, Inna Fauziatal; Ismayawati, Any; Jalil, Saidatul Najihah binti Abdul; Karim, Muchamad Busrol (El-Mashlahah, 2025)
The pak ponjen’s marriage tradition in Pasuruhan Lor Village, Kudus, is an interesting example of how Islamic law interacts with local traditions. With its strong symbolic and social values, this tradition unites the families of the bride and groom, and strengthens the social bonds of the community. The research aimed to study the meaning, usage, and legal status of the pak ponjen tradition, as well as how this tradition adapts to modern developments and globalization. This study used a qualitative field-based approach and involves seven informants from community leaders and local residents. This study found that parents express gratitude to Allah SWT for their ability to marry off their youngest child. Pak ponjen’s tradition includes sungkeman, ubengan, dulangan, giving bags, and prayers. The fact, this tradition is adapted to Islamic principles, such as the recitation of salawat and prayers, which shows a balance between customs and Islamic law. This tradition falls into the ‘urf sahih in Islamic law because it does not contradict the sharia and is beneficial to the community. Therefore, the tradition of pak ponjen not only serves as a symbol of cultural identity but also as a heritage that must be preserved while adhering to Islamic principles.